External apical root resorption assessment revisited: a scoping review - Iber-Diaz, Paula; Senen-Carramolino, Raquel; Otero-Pregigueiro, Andrea; Palma-Fernandez, Juan Carlos; Iglesias-Linares, Alejandro (The Angle orthodontist, 2025)
To provide a comprehensive critique of the diagnosis of root resorption using panoramic and periapical radiography, including discussion of the various methods of measurement, severity spectrum, and to shed light on a significant factor predisposing to resorption: treatment duration. The articles reviewed involved human subjects undergoing buccal fixed orthodontic treatment, diagnosed by panoramic or intraoral radiographs at the beginning and end of treatment. Treatment duration and external apical root resorption (EARR) had to be recorded to be included in the study. Relevant sources were searched using various platforms including PubMed, Scopus, and WoS. All sources of evidence, regardless of language, were included in the study. The search strategy yielded 704 studies; screening by title and abstract yielded 389 articles for full-text review. Forty studies were finally included and categorized according to the type of radiograph used to diagnose EARR: authors of 18 studies used panoramic radiographs, and authors of 22 studies used intraoral radiographs. In this study, we revealed a lack of agreement among authors concerning the diagnosis and measurement methods of external apical root resorption, resulting in inconsistencies in the results. Additionally, patient- and treatment-related factors, including treatment duration, were found to be inconsistently associated with the development of EARR. Standardization of diagnostic protocols and refinement of measurement techniques are essential to improve the accuracy of orthodontic care.